The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1159/000154601
|View full text |Cite
|
Sign up to set email alerts
|

Role of Amino Acid Transport System A in the Control of Cell Volume in Cultured Human Fibroblasts

Abstract: Human fibroblasts shrink and are unable to recover their initial volume when incubated in hypertonic saline solutions, whereas an efficient volume restoration takes place in hypertonic media containing substrates of the highly concentrative transport system A (amino acids and methylamines). Amino acid substrates of barely concentrative transport systems are ineffective in sustaining the volume recovery. The activity of system A increases following incubation of fibroblasts under conditions promoting cell shrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…2). However, the mechanism(s) is not well characterized and the hypertonicity-mediated effect has somehow been related to the derepression ofthe system that occurred after amino acid starvation (22,23). Results of our earlier studies (11) showed that system A activity was not expressed in NBL-1 cells exposed to hypertonic shock when cultured in Ham's F-12 Ag/ml).…”
Section: Discussionmentioning
confidence: 99%
“…2). However, the mechanism(s) is not well characterized and the hypertonicity-mediated effect has somehow been related to the derepression ofthe system that occurred after amino acid starvation (22,23). Results of our earlier studies (11) showed that system A activity was not expressed in NBL-1 cells exposed to hypertonic shock when cultured in Ham's F-12 Ag/ml).…”
Section: Discussionmentioning
confidence: 99%
“…A cell shrinkage occurring upstream of caspase-8 activation has been also induced in CEM cells by hyperosmotic stress (Fumarola, La Monica and Guidotti, unpublished results) and recently reported for Jurkat T cells treated with agonistic anti-CD95 antibodies. 41 The replacement of L-glutamine in the culture medium with 10 mM betaine, a surrogate compatible organic osmolyte, 12 fully counteracted the cell volume decrement at 3 h and allowed CEM cells to retain more than 85% of their initial volume at 6 h ( Figure 4a). Under these conditions the cells were significantly protected from apoptosis (Figure 4b,c).…”
Section: Cell Shrinkage Induces the Cd95-dependent Apoptotic Pathwaymentioning
confidence: 99%
“…12 Labeled OMG was added during the last 30 ± 40 min of incubation to control or modified mediums (see Results) whose glucose concentration had been reduced to 0.5 mM. The cells were then quickly washed twice in icecold PBS containing 0.1 mM phloretin and extracted in ice-cold 10% trichloroacetic acid.…”
Section: Cell Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of system A activity has also been described upon hypertonic incubation (11)(12)(13)(14)(15)(16). In cultured human fibroblasts (17) and human endothelial cells (18), the hypertonic increase in system A activity is responsible for the regulatory volume increase that follows cell shrinkage and restores cell volume.…”
mentioning
confidence: 99%